Influência do padrão facial na percepção da atratividade do sorriso em relação à exposição gengival avaliado por leigos e cirurgiões dentistas - Lima, Anderson Paulo Barbosa (2017)
The present study aimed to assess the influence of facial pattern in attractiveness considering the opinion of dentists and laypersons on different levels of gingival exposure. Frontal photographs of two female models (with long and balanced face) were taken. The photographs were imported in Adobe Photoshop 6.0 software package (Adobe Systems®, San José, CA, USA) to simulate gingival exposure from 0 to 6mm. The photographs underwent the analysis of 72 dentists and 24 laypersons. The analysis consisted of scaling the aesthetic attractiveness from 1 to 5 according to Likert. Kruskal-Wallis and Friedman tests were used to compare the perception of dentists and laypersons on the level of attractiveness considering the different quantity of gingival exposure. Spearman’s Correlation Coefficient was applied to associate the age of the examiners with their scaling outcomes. Differences significant statistically (p<0.05) were observed in the following levels of exposure for subjects with long face: 0mm, 4mm, 5mm, and 6mm. Laypersons were less critical compared to dentists. In subjects with balanced face, differences significant statistically (p<0.05) were observed between laypersons and dentists for the gingival exposure levels of 2mm, 4mm, 5mm and 6mm. Laypersons has less perception of gingival exposure analyzing the balanced face. Balanced face was better rated by dentists and laypersons in all the levels of gingival exposure compared to the long face. In general, laypersons were more condescending compared to dentists. Conclusion: Facial patterns influence on the evaluation of smile attractiveness. Balanced facial harmony masks the simulated gingival exposure and turns them imperceptible for laypersons